Attosecond Hard X-ray Free Electron Laser - Sandeep Kumar (Applied Sciences, 2013)
In this paper, several schemes of soft X-ray and hard X-ray free electron lasers (XFEL) and their progress are reviewed. Self-amplified spontaneous emission (SASE) schemes, the high gain harmonic generation (HGHG) scheme and various enhancement schemes through seeding and beam manipulations are discussed, especially in view of the generation of attosecond X-ray pulses. Our recent work on the generation of attosecond hard X-ray pulses is also discussed. In our study, the enhanced SASE scheme is utilized, using electron beam parameters of an XFEL under construction at Pohang Accelerator Laboratory (PAL). Laser, chicane and electron beam parameters are optimized to generate an isolated attosecond hard X-ray pulse at 0.1 nm (12.4 keV). The simulations show that the manipulation of electron energy beam profile may lead to the generation of an isolated attosecond hard X-ray of 150 attosecond pulse at 0.1 nm.